Personality traits that differentiate attendants of higher-education online courses - León, Federico R. (2017)
This study utilized the ten aspects of the Big Five personality system to detect differences in personality traits between attendants of higher education online courses and attendants of higher education face-to-face courses. Distance education theoreticians have formulated hypotheses on the personality traits that make the Autonomy, Connectedness, Diversity, and Openness attributes of the connectivist learning model attractive. 753 participants in executive extension courses of a Peruvian university in Lima (mean age = 34.62 years) filled-in an online questionnaire which included the Big Five Aspect Scales. Whereas none of the Big Five factors discriminated between attendants and non-attendants of online courses, the former emerged as significantly higher in Industriousness (an aspect of Conscientiousness) and lower in Orderliness (the second aspect of Conscientiousness) and Enthusiasm (an aspect of Extraversion) than the latter. Theoretical and practical implications of the findings are addressed and the conduct of confirmatory studies outside Peru and involving MOOCs is recommended.